Impact of iron overload on bone remodeling in thalassemia - Pokpong Piriyakhuntorn (2020)
© 2020, International Osteoporosis Foundation and National Osteoporosis Foundation. Introduction: Iron overload, a state with excessive iron storage in the body, is a common complication in thalassemia patients which leads to multiple organ dysfunctions including the bone. Iron overload-induced bone disease is one of the most common and severe complications of thalassemia including osteoporosis. Currently, osteoporosis is still frequently found in thalassemia even with widely available iron chelation therapy. Study selection: Relevant publications published before December 2019 in PubMed database were reviewed. Both pre-clinical studies and clinical trials were obtained using iron overload, thalassemia, osteoporosis, osteoblast, and osteoclast as keywords. Results: Increased ROS production is a hallmark of iron overload-induced impaired bone remodeling. At the cellular level, oxidative stress affects bone remodeling by both osteoblast inhibition and osteoclast activation via many signaling pathways. In thalassemia patients, it has been shown that bone resorption was increased while bone formation was concurrently reduced. Conclusion: In this review, reports on the cellular mechanisms of iron overload-associated bone remodeling are comprehensively summarized and presented to provide current understanding this pathological condition. Moreover, current treatments and potential interventions for attenuating bone remodeling in iron overload are also summarized to pave ways for the future discoveries of novel agents that alleviate this condition.